Integrating Microwave Heating with Foam-Mat Drying: Drying Kinetics and Optimization for Thick Foamed Mango Pulp - Saijuntha, Jatupon; Duangkhamchan, Wasan; Youryon, Pannipa; Ronsse, Frederik; Chupawa, Prarin (Trends in Sciences, 2024)
This study addresses the challenge of processing undersized or overripe mangoes by integrating microwave heating with traditional foam-mat drying technique. The study aims at investigating drying kinetics coupled with thin-layer drying modeling and influences of microwave power (300 - 600 W) and hot-air temperature (55 - 75 °C). Among ten drying models, the so-called Midilli equation fitted well with experimental data. Results showed enhanced drying process associated with microwave heating, providing reduced drying time from 600 - 700 min (for conventional hot-air mode) to 30 - 100 min (for microwave-assisted mode). Standard deviations of moisture content and dried foam thickness measured at various points revealed uneven heat distribution when using high microwave energy, evidenced by burnt spots at 600 W. Additionally, foam collapse was observed under the mild process with low microwave powers, possibly due to prolonged drying periods. Response surface methodology demonstrated that microwave power was more important factor, positively affecting effective diffusivity coefficient (Deff) while inversely influencing specific energy consumption (SEC) and color difference (DE). Deff value increased from 5.41´10-6 m²×s-1 at 300 W and 55 °C to 18.43´10-6 m²×s-1 at 600 W and 75 °C, confirming enhance drying performance. As assisted with microwave heating, drying foamed mango sample consumed less energy up to 92 %. Optimal drying parameters were determined based on balancing the enhancement of drying performance and color alteration, suggesting drying the thick foamed mango pulp at temperature of 55 °C combined with microwave heating at 520 W, which can be served as a basis for further industrial scale-up. HIGHLIGHTS Novel method for thick mango pulp snacks. Reduced drying time from 600 - 700 to 30 - 100 min. Lowered energy use to 5.83 kWh×kg-1. Optimal conditions at 520 W, 55 °C, desirability 0.669. Applied Midilli model with 99 % accuracy. GRAPHICAL ABSTRACT